INSTRUMEN BUNGA DAN BAGI HASIL DALAM DUNIA PERBANKAN - Sujian Suretno (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2019)
This paper seeks to examine the concept of interest instruments in conventional banking and profit sharing instruments in Islamic banking and their implications for investment and financing for customers in the perspective of the principle of justice in the Islamic economy. This research uses the research library method, the researcher analyzes relevant secondary data related to this discussion, data sourced from journals, books and other reading material. This study uses a phenomenological approach to describe the overall problems of people who experience them directly, in this case are banks and customers. The results showed that the interest instruments at conventional banks tend to be more unfair because the flowering system at conventional banks does not look at the profit and loss of the businesses that are run, both businesses run by banks and businesses run by customers that require working capital financing, especially the impact usury which is very dangerous for the culprit. The profit sharing instrument at Islamic banks is based on the profit and loss of the business carried out by banks and customers are considered more equitable. Even though Islamic banks still have an expected bank rate of expectation, the standard benefits for the bank's business are to support the health of financial performance.